Cooperative Societies and Households Poverty Reduction Nexus: A Study of Minna Metropolis, Niger State, Nigeria - Ijaiya, Mukaila Adebisi; Bakare-Aremu, Tunde Abubakar; Ajudua, Emmanuel Ifeanyi; Shitu, Sidikat (NIU Journal of Social Sciences, 2020)
Poverty is one of the major challenges facing the world, most especially, the third world. Government of nations have continuously come up with different economic and social policies or programmes in other to reduce the level of poverty in their countries, Nigeria inclusive. Despite these efforts, the rate of poverty World over is still alarming and on the increase. It has been acknowledged that cooperative societies have been playing a vital role in economic development most especially at medium and micro level. Using a set of co-operative society’s member’s data generated from the administration of structured questionnaire to 500 members of a cooperative, in Minna metropolis, the study examines the role of cooperative societies on poverty reduction in Minna metropolis, Niger State, Nigeria. Therefore, this paper investigates the impact of cooperative societies on household’s poverty reduction in Minna metropolis, Niger State, Nigeria, using Structural Equation Modelling approach (SEM/AMOS). The results obtained shows that cooperative society has significantly improved the living standard of its members in the study area, thus, fulfilling our a priori expectation that cooperative society has positive impact on household’s poverty reduction in the study area. This study therefore recommends the use of policy measures that would continue to make cooperative societies relevant to household’s poverty reduction in Minna metropolis, Niger State, Nigeria in particular and the world in general. Keywords: Cooperative Societies, Households, Poverty Reduction, Niger State, Nigeria, Structural Equation Modelling Approach (AMOS).